Cortical Hemodynamic Response Associated with Spatial Coding: A Near-Infrared Spectroscopy Study - Derbie, Abiot Y.; Chau, Bolton; Lam, Bess; Fang, Yun-hua; Ting, Kin-Hung; Wong, Clive Y. H.; Tao, Jing; Chen, Li-dian; Chan, Chetwyn C. H. (Brain topography, 2021)
Allocentric and egocentric are two types of spatial coding. Previous studies reported the dorsal attention network’s involvement in both types. To eliminate possible paradigm-specific confounds in the results, this study employed fine-grained cue-to-target paradigm to dissociate allocentric (aSC) and egocentric (eSC) spatial coding. Twenty-two participants completed a custom visuospatial task, and changes in the concentration of oxygenated hemoglobin (O 2 -Hb) were recorded using functional near-infrared spectroscopy (fNIRS). The least absolute shrinkage and selection operator-regularized principal component (LASSO-RPC) algorithm was used to identify cortical sites that predicted the aSC and eSC conditions’ reaction times. Significant changes in O 2 -Hb concentration in the right inferior parietal lobule (IPL) and post-central gyrus regions were common in both aSC and eSC. Results of inter-channel correlations further substantiate cortical activities in both conditions were predominantly over the right parieto-frontal areas. Together with right superior frontal gyrus areas be the reaction time neural correlates, the results suggest top-down attention and response-mapping processes are common to both spatial coding types. Changes unique to aSC were in clusters over the right intraparietal sulcus, right temporo-parietal junction, and left IPL. With the left pre-central gyrus region, be the reaction time neural correlate, aSC is likely to involve more orienting attention, updating of spatial information, and object-based response selection and inhibition than eSC. Future studies will use other visuospatial task designs for testing the robustness of the findings on spatial coding processes.